Detection of microbial growth in aseptic food products using non-invasive Tunable Diode Laser Absorption Spectroscopy (TDLAS). (March 2023) - Myintzaw, Peter; Johnson, Nicholas Brian; Begley, Máire; Callanan, Michael
Abstract: The sensitivity and reliability of Tunable Diode Laser Absorption Spectroscopy ( TDLAS) for monitoring the growth of microorganisms in real food matrices was explored. The rapid and non-destructive TDLAS equipment uses laser light to monitor carbon dioxide changes due to microbial growth in the container head space which has the additional advantage of detecting contamination in products and packaging where visual inspection is not possible. TDLAS growth detection of Bacillus fengqiuensis, Candida albicans, Lactococcus lactis, Microbacterium luteolum, Paenibacillus chitinolyticus and Staphylococcus pasteuri was studied in various Ready To Feed (RTF) infant formula products. Detection of growth was correlated with cell numbers and the reliability of detection was tested using multiple inoculum levels. Overall, detection varies based on the matrices and the characteristics of the test organisms. TDLAS was capable of detecting growth of L. lactis within 20 h and S. pasteuri in 55 h when foods were contaminated with as low as ∼100 CFU/ml. However, the spore former B. fengqiuensis was not detected after 72 h in three matrices when inoculated at low levels. The lowest cell density detected at 4.47 CFU/ml was for the yeast ( C. albicans ) after 28.99 ± 1.82 h and the highest at 8.53 CFU/mL was for the actinomycete ( M. luteolum ) at 37.02 ± 1.84 h in RTF infant formula matrices. A strong linear relationship (R 2 value ≥ 0.827) between initial inoculum and Time To Detection (TTD) for multiple inoculum levels was observed and growth rates (μ) calculated from TTD data was comparable with viable plate count methods for P. chitinolyticus but showed higher variability for L. lactis. Therefore, the TDLAS equipment was shown to be reliable with some specific limitations in identifying microbiological contamination by typical spoilage microbes in commercially sterile dairy beverage products. Highlights: Validation of Tunable Diode Laser Absorption Spectroscopy (TDLAS) for sterility testing in food. TDLAS represents a rapid and non-destructive automated sterility testing method. Sensitivity and reliability of TDLAS determined for monitoring microbial growth in aseptic foods. Tailored TDLAS settings for specific organisms and food matrices may be required.